2014
DOI: 10.1016/j.athoracsur.2014.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Standardized Perioperative Antibiotic Prophylaxis Protocol for Neonates Undergoing Cardiac Surgery

Abstract: Background A lack of perioperative antibiotic prophylaxis guidelines for neonates undergoing cardiac surgery has resulted in a wide variation in practice. We sought to: 1) determine the safety of a perioperative antibiotic prophylaxis protocol for neonatal cardiac surgery as measured by surgical site infections (SSIs) rates before and after implementation of the protocol and 2) evaluate compliance with selected process measures for perioperative antibiotic prophylaxis. Methods This quasi-experimental study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…After a careful search for references, we identified an additional 8 of 48 papers relevant for the analysis. After the removal of duplicates, exclusion of reports other than original papers or reviews, and reports that did not fulfill the inclusion criteria, we identified 20 publications for the final analysis [1][2][3][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Detailed information included in these 20 papers is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a careful search for references, we identified an additional 8 of 48 papers relevant for the analysis. After the removal of duplicates, exclusion of reports other than original papers or reviews, and reports that did not fulfill the inclusion criteria, we identified 20 publications for the final analysis [1][2][3][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Detailed information included in these 20 papers is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…What is interesting is that although some medical centers designed and implemented proper procedures, restricted observance of them could be problematic. Murray et al point to the fact that after a strict schedule implementation, timing of antibiotic prophylaxis was not proper in about 20% of patients, 27% of patients did not receive appropriate intra-operative redosing, and 84% had inadequate post-operative doses [17]. Surprisingly, after the implementation of an antibiotic prophylaxis protocol in this special group of patients, some authors observe that additional antibiotics for empirical treatment are initiated more often after the intervention than before (26.9% vs. 18.6%, respectively) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 14 studies (12%) evaluated a pediatric population, [33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 111 (88%) evaluated an adult, mixed (adult and pediatric), or undefined population. We quantified the studies by surgical specialty: 21 cardiothoracic, 33,36,37,39,40,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] 22 orthopedic, 34,41,42,[62][63][64][65][66][67][68][69][70][71][72][73][74]...…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The 48 hour course has been shown to be similar to a 5 day course in prevention of SSI hence no need for prolongation beyond 48 hours [29][30][31]. Prolonged administration of antibiotics postoperatively was associated with complications including diarrhea due to Clostridium difficile colitis [32].…”
mentioning
confidence: 99%